A correlative study of gliomas using in vivo bromodeoxyuridine labeling index and computer-aided malignancy grading - Sharma, Suash; Schmitt, Horst Peter (Pathology & oncology research, 2002)
An in vivo bromodeoxyuridine (BrdU) labeling index (LI) was estimated in 43 cases of astrocytic tumors and mixed gliomas by one hour intra-operative intravenous infusion at a dose of 200 mg/m2and correlated with (a) histological grading using a computer aided malignancy classifier TESTAST-268; and (b) histological typing using WHO classification. The lowest BrdU LI was seen in pilocytic and gemistocytic astrocytomas followed by astrocytomas, anaplastic astrocytomas and glioblastoma multiforme in that order. Mixed oligoastrocytomas followed the pattern of their astrocytic counterparts. Tumors of similar histological type showed different BrdU LI values especially amongst astrocytomas and glioblastomas. A statistically significant difference in the BrdU LI was also noted between the higher TESTAST grades of astrocytomas (T III and IV) versus the lower TESTAST grades (T II). Unlike earlier reports in literature, in the present study the category of BrdU LI of5 contained only anaplastic astrocytoma and glioblastoma multiforme (TESTAST grades III and IV). Maximum spread of cases was seen in the BrdU LI category of 1-5, not only in terms of histological types but also TESTAST grades. Thus there appeared to be a positive trend of increasing BrdU LI values both with histological types and increasing TESTAST grades. Further, an interesting observation was that by using a combination of TESTAST grades and BrdU LI, the histologically homogenous glioblastoma group could be further subdivided into 4 categories which showed a trend towards prognostic correlation. Thus, this study though preliminary with number of cases being small in some groups, highlights the possible usefulness of combined histological typing, TESTAST grading and in vivo BrdU LI for prognostication of gliomas especially glioblastoma multiforme. Copyright 1999 W.B. Saunders Company Ltd on behalf of the Arányi Lajos Foundation
Gesehen am 27.11.2017